2019
DOI: 10.1103/physrevb.99.094512
|View full text |Cite
|
Sign up to set email alerts
|

Observation of subkelvin superconductivity in Cd3As2 thin films

Abstract: We report the first experimental observation of superconductivity in Cd3As2 thin films without application of external pressure. Surface studies suggest that the observed transport characteristics are related to the polycrystalline continuous part of investigated films with homogeneous distribution of elements and the Cd-to-As ratio close to stoichiometric Cd3As2. The latter is also supported by Raman spectra of the studied films, which are similar to those of Cd3As2 single crystals. The formation of supercond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 40 publications
9
21
0
3
Order By: Relevance
“…The energy-dispersive X-ray (EDX) spectroscopy results demonstrated that the Cd and As distributed homogeneously within the film, while the actual elemental composition is close to the stoichiometric Cd 3 As 2 within 2% accuracy (corresponding results include both averaging over large surface areas and analysis in points with different contrast). Described SEM results are very close to those reported earlier for magnetron-sputtered f ilms 20 . The crystal structure of studied films were investigated using X-ray diffraction (XRD) measurements (see Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The energy-dispersive X-ray (EDX) spectroscopy results demonstrated that the Cd and As distributed homogeneously within the film, while the actual elemental composition is close to the stoichiometric Cd 3 As 2 within 2% accuracy (corresponding results include both averaging over large surface areas and analysis in points with different contrast). Described SEM results are very close to those reported earlier for magnetron-sputtered f ilms 20 . The crystal structure of studied films were investigated using X-ray diffraction (XRD) measurements (see Fig.…”
Section: Resultssupporting
confidence: 89%
“…However, one can distinguish three pronounced peaks (marked by green circles in Fig. 1b 20 , we argued that the polycrystalline nature of samples was partially related to the presence of both α and α′ phases. Corresponding XRD patterns also indicated partial orientation of Cd 3 As 2 crystallites with the average size of about 35 nm.…”
Section: Resultsmentioning
confidence: 82%
“…This characteristic is similar to that of the interfacial superconductivity previously reported in SrTiO 3 /LaAlO 3 system [ 33 ] and that of the superconducting Cd 3 As 2 film. [ 34 ] The critical current was determined to be about 0.9 milliampere. Figure 1e presents a series of ZBR– T curves measured at different magnetic fields.…”
Section: Figurementioning
confidence: 99%
“…Методом фотоэлектронной спектроскопии с угловым разрешением было показано, что Cd 3 As 2 обладает всеми перечисленными выше особенностями электронной структуры [7], что также подтверждается результатами зон-ных расчетов из первых принципов [8]. Кроме того, в Cd 3 As 2 наблюдался целый ряд необычных явлений, включая киральную аномалию, гигантское магнетосопротивление, а также недавно обнаруженную нетривиальную сверхпроводимость [9,10]. В отличие от Na 3 Bi, кристаллы Cd 3 As 2 стабильны на воздухе, что делает их более привлекательными для исследования.…”
Section: Introductionunclassified